2014
DOI: 10.5812/ijhrba.21076
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ecstasy on Liver Function Tests, Blood Glucose, and Lipids Profile of Male Rats

Abstract: Background:Ecstasy is used to improve mood and cordiality; however, based on some reports, it is neurotoxic to human users.Objectives:Because of the euphoria induced by MDMA (3,4-methylenedioxymethamphetamine) on the users, its consumption is increasing in almost all countries. This study was carried out to determine the effects of ecstasy administration in rats’ blood sugar, lipids profile, and liver function tests.Materials and Methods:The experiment was performed using 50 mature Wistar-Albino male rats. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although the pathogenesis is unclear, our data suggested that high levels of AST and ALT in serum are due to hepatic injury caused by long-term simulated weightlessness. AST and ALT are liver enzyme markers, which indicate the health condition of hepatocytes [ 28 ]. When hepatocellular injury or death, release of hepatic enzymes from damaged hepatocytes increase levels of ALT and ALT in serum [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis is unclear, our data suggested that high levels of AST and ALT in serum are due to hepatic injury caused by long-term simulated weightlessness. AST and ALT are liver enzyme markers, which indicate the health condition of hepatocytes [ 28 ]. When hepatocellular injury or death, release of hepatic enzymes from damaged hepatocytes increase levels of ALT and ALT in serum [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the end of result of apoptotic effects expected to yield liver injury, one may also evaluate controlled studies in humans and animal models for evidence of potential hepatotoxicity. For example, ephedrine and pseudoephedrine decreased liver injury markers (e.g, alanine aminotransferase or ALT and bilirubin) in experimentally induced acute liver injury in Wistar rats [83], while methamphetamine and MDMA are known to increase liver injury markers and demonstrate histological changes indicative of injury in rats [87,110,111]. In Wistar rats given a formulation containing 1,3-dimethylamylamine, no changes were found in ALT, aspartate aminotransferase (AST) and gamma-glutamyl transferase (GGT).…”
Section: Mechanism Of Amphetamine-induced Hepatotoxicitymentioning
confidence: 99%
“…Severity of liver injury is not in direct correlation with the amount of ingested substance, or with the frequency of intake, which points to idiosyncratic type of reaction. It can also cause fever, which was registered with our patient [14,15]. He was also using whey protein and creatine, which are known for causing liver injury, especially cholestatic type with expressed jaundice.…”
Section: Discussionmentioning
confidence: 72%